Innovative Leadership Practices of Early Childhood Education Principals in Enhancing Teacher Productivity - Bahera; Ahmad Syukri; Mahmud My; Arief Al Hazmi Adlan (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aims to explore the role of leadership in improving teacher productivity at TK Islam Al-Azhar Jambi. Early Childhood Education (PAUD) plays a crucial role in laying the foundation for children's development, and effective leadership from PAUD principals is essential to ensure high-quality education. This research uses a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings reveal that the principal's leadership significantly influences teacher productivity through several key managerial factors, including managerial competence, professional development strategies, leadership style, motivation, communication, and a positive work environment. The ability of the PAUD principal to implement transformational leadership, build effective communication, and foster a supportive atmosphere directly contributes to teachers’ motivation, confidence, and overall performance. This study highlights the importance of strengthening leadership capacity in PAUD institutions to enhance the quality of early childhood education.